Wspomnienie młodości. O znaczeniu przysłowia "Przypomniała baba dziewic wieczór" w utworach Elizy Orzeszkowej = The memory of the youth. On the meanings of the proverb "the old woman recalled the evening of the virgins" in Eliza Orzeszkowa's works - Kaczor, Monika; Narolska, Aneta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The subject of the article is a linguistic and literary historical analysis of the proverb "The old woman recalled the evening of the virgins" included in Eliza Orzeszkowa's writings. The first part of the work is devoted to linguistic analysis of the abovementioned proverb. The analysis confirms that its main goal is an expression of emotions associated with awareness of passing of life.
Keywords: Orzeszkowa, Eliza (1841-1910) - twórczość; przysłowie; językowy obraz świata; młodość; starość; wartościowanie; proverb; linguistic picture of the world; evaluation; the youth; the old age